Pengaruh Store Atmosphere dan Kualitas Pelayanan terhadap Kepuasan Konsumen Lawless Burgerbar Kemang Jakarta Selatan - Maxmillianus Emmanuel; Anjar Dwi Astono (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
This study aims to determine how much influence the store atmosphere and service quality have on customer satisfaction at Lawless Burgerbar Kemang, South Jakarta. This research is a quantitative approach using the SPSS Static 25 program with a total sample of 185 respondents. By using nonprobability sampling and purposive techniques. The results of this study indicate that the store atmosphere and service quality significantly affect customer satisfaction.